Window to Heart; Ocular Manifestations of Hypertension - Ma, Dae Joong; Yu, Hyeong Gon (Hanyang medical reviews, 2016)
Systemic hypertension affects not only the heart, kidneys, brain, and large arteries but also the eyes. High blood pressure (BP) causes a series of pathophysiological changes in the retinal vasculature, including focal and diffuse narrowing of the retinal arteriole, opacification of the arteriolar wall, and compression of the venules by arterioles. In severe cases, hemorrhage, nerve fiber layer infraction, and disc swelling can occur. Systemic hypertension results in various retinal vascular diseases, such as hypertensive retinopathy, retinal vein or artery occlusion, retinal arterial macroaneurysm, and nonarteritic ischemic optic neuropathy. High BP also increases the risk of development and progression of diabetic retinopathy. Signs of hypertensive retinopathy are predictive of target-organ damages, including cardiovascular and cerebrovascular diseases. While managing patients with hypertensive retinopathy, physicians should be aware of the management of cardiovascular and cerebrovascular risk factors. KCI Citation Count: 1